Preparation method of microcarrier
The sodium hyaluronate and chitosan microcarriers prepared through emulsification and crosslinking reactions solved the problems of unstable charge and unsuitable structure of existing microcarriers in cell culture, and achieved good adhesion and growth of cells.
Patent Information
- Application Number
- CN202510071611.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
AI Technical Summary
Existing microcarriers have surface charge instability, non-porous structures and unsuitable surface roughness in cell culture, limiting cell growth and differentiation.
A mixed solution of sodium hyaluronate and chitosan was prepared, emulsified and cured, to form microspheres, and a stable microcarrier was formed by cross-linking reaction, and finally washed and dried.
The prepared microcarriers have high crosslinking, stable charge state, porous structure and suitable surface roughness, which promotes cell adhesion and growth and are suitable for the cultivation of a variety of cells.
Smart Images

Figure CN119823935A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cell culture, and in particular to a method for preparing a microcarrier. Background Art
[0002] Cell microcarriers generally refer to microspheres with a diameter of 60-250μm, which are suitable for the growth of adherent cells. Microcarrier culture technology was used for large-scale animal cell culture in 1967. It is currently widely used in the production of vaccines, genetic engineering products, etc. Microcarrier culture is currently recognized as the most promising large-scale animal cell culture technology. It has the advantages of both suspension culture and adherent culture and is easy to scale up. Currently, microcarrier culture is widely used to culture various types of cells and produce vaccines and protein products.
[0003] Studies have shown that the surface characteristics of microcarriers are key factors affecting cell growth and differentiation, including surface charge, functional groups, roughness, comparative area, matrix stiffness, etc. The basic factor controlling cell adhesion is the charge density of the microcarrier surface. Studies have shown that adsorption on the surface of charged -COOH and -NH2 functional groups is conducive to protein adsorption and promotes cell adhesion. If the charge density is too low, cell adhesion is insufficient. However, if the charge density is too high, it will produce a "toxic" effect. For example, chitosan and sodium hyaluronate carry positive and negative charges respectively, and both have very high charge density. When cells are cultured, cells aggregate to resist the influence of high-density charges, which is not conducive to cell growth.
[0004] Sodium hyaluronate (HA) is an important component of the human body and is an acidic polysaccharide with a negative charge; chitosan (CS) is a biomaterial extracted from shrimp and crab shells and is an alkaline polysaccharide with a positive charge. When the two are mixed in a solution state, electrostatic polymerization will occur. Its unique amphoteric structure has attracted widespread attention. Many studies have prepared HA-CS electrostatic polymers by electrospinning, 3D printing, etc., and studied the different properties of gel polymers. However, HA-CS electrostatic polymers are bound together by electrostatics, which is not a stable state. They will depolymerize under hypertonic conditions or alkaline conditions (chitosan is not positively charged under alkaline conditions). At the same time, the electrostatically bound sodium hyaluronate chitosan polymer, due to the unstable state of electrostatic binding, is in a repulsive state when in contact with cells, limiting its application in biomedicine.
[0005] Sodium hyaluronate molecules contain carboxyl groups, and chitosan contains amino groups. Under the action of a dehydrating agent, dehydration can occur to form amide bonds. Patent CN 113663126 A uses this principle to prepare sodium hyaluronate gel microspheres using chitosan as a crosslinking agent; Patent CN 114081989 B uses microfluidic technology to crosslink chitosan and sodium hyaluronate to prepare degradable embolic microspheres. Patent CN 115845120 A uses activated sodium hyaluronate as a crosslinking agent to crosslink chitosan to prepare cationic microspheres.
[0006] However, the microspheres prepared by the above technology are not for cell culture applications, are not suitable for cell culture, and cannot meet the requirements of cell culture. Cell microcarriers require finely regulated surface charge states to increase cell adhesion; they require porous structures, appropriate surface roughness, and matrix stiffness to simulate the in vivo cell niche to the maximum extent possible and ensure cell growth. Therefore, it is necessary to propose a new microcarrier preparation method, which can produce microcarriers that meet the requirements of cell culture, adapt to the adhesion and growth of a variety of cells, and ensure cell adhesion, growth, and value-added. Summary of the invention
[0007] The present invention has developed a new method for preparing microcarriers in view of the defects and deficiencies of the above-mentioned microcarriers, and the preparation method comprises the following steps: S1: preparing a first mixed solution, wherein the first mixed solution comprises a sodium hyaluronate solution and a chitosan solution; S2: emulsifying the first mixed solution to obtain an emulsified solution; S3: solidifying the emulsified solution to form microspheres; S4: treating the microspheres to cause a cross-linking reaction to form microcarriers; S5: cleaning and drying the microcarriers. The beneficial effect is that the preparation method uses sodium hyaluronate and chitosan as raw materials, and the microcarriers prepared therefrom are absorbable and degradable, with a degradation time of 6 to 12 months, and have good biocompatibility. The cultured microcarrier-cell complex can be directly used as the final product for clinical transformation without removing the cells.
[0008] In some embodiments, the S1 includes: S11: dissolving sodium hyaluronate in a monovalent metal salt solution to obtain the sodium hyaluronate solution; S12: dissolving chitosan in a monovalent metal salt acetic acid solution to obtain the chitosan solution; S13: mixing the sodium hyaluronate solution and the chitosan solution to obtain the first mixed solution. Its beneficial effect is that since each unit in the chitosan molecule contains a positive charge and every two units of sodium hyaluronate contain a negative charge, due to the excessively high charge density, it is easy for the materials to be mutually coated and stacked, and it is difficult to achieve orderly combination of materials and a high cross-linking density. In order to achieve a high degree of cross-linking and a stable charge state of the microcarrier, sodium hyaluronate and chitosan are dissolved in a metal salt solution, and the electrostatic interaction between the two is removed by the electrostatic coagulation agent metal salt ions, and the mixture is mixed into a uniform solution, rather than electrostatically combining to form a precipitate.
[0009] In some embodiments, the step S2 includes: S21: adding an oil phase and an emulsifier into a container and mixing them; S22: adding the first mixed solution into the container and stirring and emulsifying to obtain the emulsified solution. The beneficial effect is that the solution is prepared into droplets of a certain particle size by an emulsification method.
[0010] In some embodiments, S3 includes: S31: adding a first hydrophilic organic solvent to the emulsified solution to solidify and form microspheres; S32: leaching the microspheres; S33: washing the microspheres with a second hydrophilic organic solvent. The beneficial effect is that the electrostatic polymerization agent metal salt ions in the droplets are washed away with the first hydrophilic organic solvent, and chitosan sodium hyaluronate is subjected to in-situ orderly electrostatic polymerization to form solid microspheres. After the microspheres are leached out of the emulsified solution, the microspheres are washed with a second hydrophilic organic solvent to completely remove the metal salt particles in the microspheres. The metal salt particles in the microspheres are completely removed by washing with the first hydrophilic organic solvent and the second hydrophilic organic solvent gradient, so as to achieve highly ordered in-situ electrostatic bonding of chitosan sodium hyaluronate.
[0011] In some embodiments, the S4 includes: S41: adding a catalyst to a third hydrophilic organic solvent; S42: adding the microspheres to the third hydrophilic organic solvent for cross-linking reaction to generate the microcarriers. The beneficial effect is that the electrostatic polymerization in the solid microspheres is an unstable structure, and a water molecule in the electrostatic binding part can be removed by the catalyst to achieve in-situ cross-linking to form a stable chemical bond amide bond, and the subsequent in-situ cross-linking is combined on the basis of highly ordered electrostatic binding, and finally a cross-linking degree greater than 50% is achieved.
[0012] In some embodiments, the step S5 includes: S51: washing the microcarriers with a fourth hydrophilic organic solvent; S52: drying the washed microcarriers. The beneficial effect is that the fourth hydrophilic organic solvent is used to wash and remove the attached impurities on the microcarriers.
[0013] In some embodiments, the concentration of the monovalent metal salt in the monovalent metal salt solution is 0.5-2 mol / L, the mass percentage of acetic acid in the monovalent metal salt acetic acid solution is 0.5-3%; the concentration of the sodium hyaluronate solution is 0.5%-10%, and the concentration of the chitosan solution is 0.5%-10%.
[0014] In some embodiments, the monovalent metal salt includes at least one of sodium chloride and potassium chloride.
[0015] In some embodiments, the oil phase includes at least one of liquid paraffin, mineral oil and vegetable oil; and the emulsifier includes at least one of sorbitan monooleate polyoxyethylene ether and sorbitan oleate.
[0016] In some embodiments, the mass ratio of the oil phase to the emulsifier is (35~45):1; the mass ratio of the oil phase to the first mixed solution is 1:(4~10); the stirring rate of the emulsification is 500rpm~2000rpm, and the stirring time of the emulsification is 2h~8h.
[0017] In some embodiments, the first hydrophilic organic solvent, the second hydrophilic organic solvent, the third hydrophilic organic solvent, and the fourth hydrophilic organic solvent all include at least one of ethanol, acetone, and dimethylformamide.
[0018] In some embodiments, the concentration of the first hydrophilic organic solvent is 75% to 95%, and the volume ratio of the first hydrophilic organic solvent to the oil phase is (0.8 to 1.2): 1; the addition rate of the first hydrophilic organic solvent is 10 ml / min to 100 ml / min, and stirring is continued during the addition of the first hydrophilic organic solvent, the stirring rate is 100 rpm to 800 rpm, and the stirring time is 1 h to 15 h.
[0019] In some embodiments, the concentration of the second hydrophilic organic solvent is 30% to 75%, and the mass ratio of the second hydrophilic organic solvent to the microspheres is (10 to 50): 1; the number of cleaning times is 1 to 5 times, and the time for each cleaning is 1 to 4 hours.
[0020] In some embodiments, the catalyst includes 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysulfosuccinimide (NHS), and the concentration of the catalyst is 0.5‰~4‰.
[0021] In some embodiments, the concentration of the third hydrophilic organic solvent is 75% to 95%.
[0022] In some embodiments, the temperature of the cross-linking reaction is 10° C. to 50° C., and the time of the cross-linking reaction is 5 h to 24 h.
[0023] In some embodiments, the concentration of the fourth aqueous organic solvent is 100%.
[0024] The beneficial effects of the present invention are that the microcarrier prepared by the preparation method of the present invention has the following advantages: 1. A cross-linking degree of 50% achieves a stable material state and relatively improves the matrix stiffness of the microcarrier, which is more conducive to cell migration.
[0025] 2. The microcarrier is degradable and the degradation time is 6 to 12 months.
[0026] 3. The microcarrier has a three-dimensional mesh structure with extremely high porosity and surface roughness. The porosity is greater than 85%, which can promote the adsorption of proteins and thus promote the adhesion of cells.
[0027] 4. The charge type and charge density of the microcarrier can be adjusted not only according to different cells, but also according to different application scenarios or cell differentiation requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The flowchart of the preparation method of the microcarrier of the embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of a microcarrier according to an embodiment of the present invention; Figure 3 This is a diagram of the three-dimensional mesh structure of the microcarrier according to an embodiment of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the usual meanings understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Unless otherwise specified, the "connection" described in this article can be a direct connection or an indirect connection, that is, connected through an intermediate.
[0030] In view of the problems existing in the prior art, the embodiments of the present invention provide a method for preparing a microcarrier. Figure 1 The present invention provides a method for preparing a microcarrier, which comprises the following steps: S1: preparing a first mixed solution, wherein the first mixed solution comprises a sodium hyaluronate solution and a chitosan solution; S2: emulsifying the first mixed solution to obtain an emulsified solution; S3: solidifying the emulsified solution to form microspheres; S4: treating the microspheres to cause a cross-linking reaction to form microcarriers; S5: cleaning and drying the microcarriers.
[0031] In some embodiments, the S1 includes: S11: dissolving sodium hyaluronate in a monovalent metal salt solution to obtain the sodium hyaluronate solution; S12: dissolving chitosan in a monovalent metal salt acetic acid solution to obtain the chitosan solution; S13: mixing the sodium hyaluronate solution and the chitosan solution to obtain the first mixed solution.
[0032] In this embodiment, the ratio of the sodium hyaluronate to the chitosan is preferably 2:1. Both chitosan and sodium hyaluronate have a large amount of net charge. When the two materials are used alone as medical materials, they are not conducive to the adhesion and growth of cells due to their large amount of positive or negative charges. Chitosan and sodium hyaluronate will produce electrostatic bonding to form a polymer. By regulating the ratio of positive and negative charge groups in the network structure, the polymer exhibits unique polyelectrolyte properties and anti-polyelectrolyte properties (near the isoelectric point). When the ratio of positive charge to negative charge is close (when the ratio of sodium hyaluronate to chitosan is about 2:1), its unique amphiphilic structure and corresponding properties are closer to natural polymers.
[0033] In some embodiments, the S2 includes: S21: adding an oil phase and an emulsifier into a container and mixing; S22: adding the first mixed solution into the container and stirring and emulsifying to obtain the emulsified solution.
[0034] In this embodiment, when the first mixed solution is added into the container, stirring may be performed while adding the first mixed solution, and the first mixed solution may be emulsified during the stirring process.
[0035] In some embodiments, the S3 comprises: S31: adding a first hydrophilic organic solvent to the emulsified solution to solidify and form microspheres; S32: leaching out the microspheres; S33: washing the microspheres with a second hydrophilic organic solvent.
[0036] In this embodiment, reference Figure 2, a first hydrophilic organic solvent is added to the emulsified solution to solidify the emulsified solution to form the microspheres. The emulsified solution is not solidified as a whole, but solidified to form a plurality of microspheres. At this time, there are unsolidified emulsified solution and solidified microspheres in the container, and the microspheres can be leached out using a filtering device.
[0037] In some embodiments, the S4 includes: S41: adding a catalyst to a third hydrophilic organic solvent; S42: adding the microspheres to the third hydrophilic organic solvent for cross-linking reaction to generate the microcarriers.
[0038] In this embodiment, the cross-linking reaction of the microspheres refers to removing a water molecule in the electrostatic bonding part of chitosan and sodium hyaluronate to form a stable chemical bond amide bond, and the microspheres are gradiently cleaned and solidified by a first hydrophilic organic solvent and a second hydrophilic organic solvent to achieve highly ordered electrostatic bonding of chitosan and sodium hyaluronate in situ combined with subsequent in situ cross-linking, and finally a cross-linking degree greater than 50% is achieved.
[0039] In some embodiments, the S5 comprises: S51: washing the microcarriers with a fourth hydrophilic organic solvent; S52: drying the washed microcarriers.
[0040] In some embodiments, the concentration of the monovalent metal salt in the monovalent metal salt solution is 0.5-2 mol / L, the mass percentage of acetic acid in the monovalent metal salt acetic acid solution is 0.5-3%; the concentration of the sodium hyaluronate solution is 0.5%-10%, and the concentration of the chitosan solution is 0.5%-10%.
[0041] In some embodiments, the monovalent metal salt includes at least one of sodium chloride and potassium chloride.
[0042] In some embodiments, the oil phase includes at least one of liquid paraffin, mineral oil and vegetable oil. The emulsifier includes at least one of sorbitan monooleate polyoxyethylene ether and sorbitan oleate.
[0043] In this embodiment, the oil phase refers to an oil-based liquid. In addition to liquid paraffin, mineral oil and vegetable oil, other oil-based liquids can also meet the requirements of this embodiment.
[0044] In some embodiments, the mass ratio of the oil phase to the emulsifier is (35-45):1, preferably 40:1; the mass ratio of the oil phase to the first mixed solution is 1:(4-10).
[0045] The stirring rate of the emulsification is 500 rpm to 2000 rpm, and the stirring time of the emulsification is 2 h to 8 h.
[0046] In some embodiments, the first hydrophilic organic solvent, the second hydrophilic organic solvent, the third hydrophilic organic solvent, and the fourth hydrophilic organic solvent all include at least one of ethanol, acetone, and dimethylformamide.
[0047] In some embodiments, the concentration of the first hydrophilic organic solvent is 75%-95%, and the volume ratio of the first hydrophilic organic solvent to the oil phase is (0.8-1.2):1, preferably 1:1.
[0048] The addition rate of the first hydrophilic organic solvent is 10 ml / min to 100 ml / min, and stirring is performed continuously during the addition of the first hydrophilic organic solvent. The stirring rate is 100 rpm to 800 rpm, and the stirring time is 1 h to 15 h.
[0049] In some embodiments, the concentration of the second hydrophilic organic solvent is 30% to 75%, and the mass ratio of the second hydrophilic organic solvent to the microspheres is (10 to 50): 1; the number of cleaning times is 1 to 5 times, and the time for each cleaning is 1 to 4 hours.
[0050] In some embodiments, the catalyst includes 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysulfosuccinimide (NHS), and the concentration of the catalyst is 0.5‰~4‰.
[0051] In some embodiments, the concentration of the third hydrophilic organic solvent is 75% to 95%.
[0052] In some embodiments, the temperature of the cross-linking reaction is 10° C. to 50° C., and the time of the cross-linking reaction is 5 h to 24 h.
[0053] In some embodiments, the concentration of the fourth aqueous organic solvent is 100%.
[0054] In a second aspect, the present invention provides a microcarrier. An embodiment of the present invention provides a microcarrier comprising sodium hyaluronate and chitosan, wherein the sodium hyaluronate and the chitosan are cross-linked with each other; wherein the ratio of the sodium hyaluronate to the chitosan is (1.5-2.5): 1, and the degree of cross-linking between the sodium hyaluronate and the chitosan is greater than 50%.
[0055] In this embodiment, the chitosan and the sodium hyaluronate are natural polymer materials, and the raw materials are easily obtained. The microcarrier prepared from the chitosan and the sodium hyaluronate is absorbable and degradable, and the degradation time is 6 to 12 months, and has good biocompatibility.
[0056] In some embodiments, the diameter of the microcarrier is 10µm to 1000µm.
[0057] In this embodiment, reference Figure 2 , the diameter of the microcarrier ranges from 10µm to 1000µm.
[0058] In some embodiments, the microcarrier is a three-dimensional mesh structure. Figure 3 , its porosity is greater than 85%.
[0059] In this embodiment, reference Figure 3 The microcarrier with three-dimensional mesh structure can provide a higher surface area, and the porous environment can better simulate the cell niche of stem cell culture in vitro. The porosity is greater than 85%, which can promote protein adsorption and then promote cell adhesion to ensure subsequent cell proliferation.
[0060] In some embodiments, the charge density of the microcarrier is -50 μeq / g to +71 μeq / g.
[0061] In this embodiment, within the charge range of the microcarriers, the charge type and charge density of the microcarriers can be adjusted according to the different subsequent cultured cells.
[0062] In a third aspect, an embodiment of the present invention provides an application of a microcarrier in preparing exosomes.
[0063] In this embodiment, a dynamic suspension culture method can be used to culture cells using the microcarrier; after culture, the microcarrier-cell complex is separated by filtration or centrifugation, and the cell culture supernatant is collected; finally, the supernatant is used for extracting exosomes by ultracentrifugation.
[0064] The present invention is further described below by specific examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be obtained commercially, and the reagents and materials involved can also be synthesized by conventional synthesis methods.
[0065] Example 1 1) Dissolve sodium hyaluronate in 1 mol / L sodium chloride solution to a concentration of 1%; dissolve chitosan in 1 mol / L sodium chloride 1% acetic acid solution to a chitosan solution concentration of 5%. Mix the two solutions, with the mass ratio of sodium hyaluronate to chitosan being 2:1.
[0066] 2) Add 2% sorbitan oleate to liquid paraffin, then add the mixed solution to stir and emulsify, the mass ratio of the mixed solution to the oil phase is 1:6, the emulsification stirring rate is 1500 rpm, and the emulsification stirring time is 8 hours.
[0067] 3) The stirring speed was adjusted to 100 rpm, and during the stirring process, a first hydrophilic organic solvent (acetone) having an equal volume to the oil phase was added at a rate of 80 ml / min with a concentration of 85%, and the curing time was 5 h.
[0068] 4) Add the leached microspheres to a 50% concentration of a second hydrophilic organic solvent (dimethylformamide) at a concentration of 30 times (to the mass ratio of the microspheres), and wash for 3 hours, 3 times. 5) Dissolve 1‰ of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysulfosuccinimide (NHS) in 85% ethanol solution, add the cleaned microcarriers, and crosslink at 10°C for 24h. The cross-linked microcarriers were washed with anhydrous ethanol solution and dried to obtain polymer microcarriers. The average particle size of the microcarriers was observed and measured using a scanning electron microscope, and the surface charge density of the microcarriers was tested using a particle charge tester. The infrared spectrum of the microcarriers was tested using a Fourier transform infrared spectrometer.
[0069] Crosslinking degree test method: Principle of cross-linking degree test: The trinitrobenzene sulfonic acid (TNBS) method is a method for determining the content of free amino groups in proteins. The TNBS method is based on the quantitative reaction of amino groups with TNBS. TNBS reacts with amino groups under weak alkaline conditions to form an intermediate complex with a chromophore. The intermediate complex has maximum absorption values near 355 nm and 420 nm.
[0070] Test steps: 1) Take 20 mg of microcarriers, add 5 ml of 0.1 M sodium bicarbonate solution, pH 8.5, and then add 5 ml of 0.5% TNBS solution by volume, and react at 40°C for 2 hours.
[0071] 2) After the reaction is completed, add 15 ml of 6M hydrochloric acid and incubate at 60°C for 1.5 hours.
[0072] 3) After the reaction is completed, wait for the reaction solution to cool to room temperature, then add 25 ml of deionized water and mix evenly.
[0073] 4) Take out 5 ml of the mixed solution into a test tube, add 10 ml of ether, shake evenly and let it stand, wait for the liquid to separate, and then take out the upper layer of ether. Then, add 10 ml of ether and repeat the above steps three times. After the ether in the reaction solution is completely volatilized, observe the absorbance of the reaction solution at a wavelength of 345 nm. And compare it with the uncrosslinked microcarrier.
[0074] The cross-linking degree is calculated as follows: (AB) / A*100%; wherein: A: absorbance of the uncross-linked microcarrier; B: absorbance of the microcarrier.
[0075] Embodiment 2-4 The difference between it and Example 1 is that the ratio of sodium hyaluronate concentration to chitosan concentration is different, and the conditions in the preparation process are also different; the specific ratios of Example 2, Example 3 and Example 4 can be seen in Table 1.
[0076] Table 1
[0077] The average particle size, surface charge density and cross-linking degree of the microcarriers of Example 1, Example 2, Example 3 and Example 4 are shown in Table 2.
[0078] Table 2
[0079] The above is only a specific implementation of the embodiment of the present application, but the protection scope of the embodiment of the present application is not limited thereto, and any changes or replacements within the technical scope disclosed in the embodiment of the present application should be included in the protection scope of the embodiment of the present application. Therefore, the protection scope of the embodiment of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a microcarrier, characterized in that: The following steps are involved: S1: preparing a first mixed solution, wherein the first mixed solution comprises a sodium hyaluronate solution and a chitosan solution; S2: emulsifying the first mixed solution to obtain an emulsified solution; S3: solidifying the emulsified solution to form microspheres; S4: treating the microspheres to cause a cross-linking reaction to form microcarriers; S5: washing and drying the microcarriers.
2. The method for preparing a microcarrier according to claim 1, characterized in that: The S1 includes: S11: dissolving sodium hyaluronate in a monovalent metal salt solution to obtain the sodium hyaluronate solution; S12: dissolving chitosan in a monovalent metal salt acetic acid solution to obtain the chitosan solution; S13: mixing the sodium hyaluronate solution and the chitosan solution to obtain the first mixed solution.
3. The method for preparing a microcarrier according to claim 1, characterized in that: The S2 includes: S21: adding the oil phase and the emulsifier into a container and mixing; S22: adding the first mixed solution into the container and stirring and emulsifying to obtain the emulsified solution.
4. The method for preparing a microcarrier according to claim 1, characterized in that: The S3 includes: S31: adding a first hydrophilic organic solvent to the emulsified solution to solidify and form microspheres; S32: leaching out the microspheres; S33: washing the microspheres with a second hydrophilic organic solvent.
5. The method for preparing a microcarrier according to claim 1, characterized in that: The S4 includes: S41: adding a catalyst to a third hydrophilic organic solvent; S42: adding the microspheres into the third hydrophilic organic solvent to perform a cross-linking reaction to generate the microcarriers.
6. The method for preparing a microcarrier according to claim 1, characterized in that: The S5 includes: S51: washing the microcarrier using a fourth hydrophilic organic solvent; S52: Drying the washed microcarriers.
7. The method for preparing a microcarrier according to claim 2, characterized in that: The concentration of the monovalent metal salt in the monovalent metal salt solution is 0.5-2 mol / L, and the mass percentage of acetic acid in the monovalent metal salt acetic acid solution is 0.5-3%; The concentration of the sodium hyaluronate solution is 0.5%-10%, and the concentration of the chitosan solution is 0.5%-10%.
8. The method for preparing a microcarrier according to claim 7, characterized in that: The monovalent metal salt includes at least one of sodium chloride and potassium chloride.
9. The method for preparing a microcarrier according to claim 3, characterized in that: The oil phase comprises at least one of liquid paraffin, mineral oil and vegetable oil; The emulsifier includes at least one of sorbitan monooleate polyoxyethylene ether and sorbitan oleate.
10. The method for preparing a microcarrier according to claim 9, characterized in that: The mass ratio of the oil phase to the emulsifier is (35-45):1; the mass ratio of the oil phase to the first mixed solution is 1:(4-10); The stirring rate of the emulsification is 500 rpm to 2000 rpm, and the stirring time of the emulsification is 2 h to 8 h.
11. The method for preparing a microcarrier according to any one of claims 4 to 6, characterized in that: The first hydrophilic organic solvent, the second hydrophilic organic solvent, the third hydrophilic organic solvent and the fourth hydrophilic organic solvent each include at least one of ethanol, acetone and dimethylformamide.
12. The method for preparing a microcarrier according to claim 3 or 4, characterized in that: The concentration of the first hydrophilic organic solvent is 75% to 95%, and the volume ratio of the first hydrophilic organic solvent to the oil phase is (0.8 to 1.2):1; The addition rate of the first hydrophilic organic solvent is 10 ml / min to 100 ml / min, and stirring is performed continuously during the addition of the first hydrophilic organic solvent. The stirring rate is 100 rpm to 800 rpm, and the stirring time is 1 h to 15 h.
13. The method for preparing a microcarrier according to claim 4, characterized in that: The concentration of the second hydrophilic organic solvent is 30% to 75%, and the mass ratio of the second hydrophilic organic solvent to the microspheres is (10 to 50): 1; The cleaning times are 1 to 5 times, and the time for each cleaning is 1 to 4 hours.
14. The method for preparing a microcarrier according to claim 5, characterized in that: The catalyst includes 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysulfosuccinimide (NHS), and the concentration of the catalyst is 0.5‰~4‰.
15. The method for preparing a microcarrier according to claim 5, characterized in that: The concentration of the third hydrophilic organic solvent is 75% to 95%.
16. The method for preparing microcarriers according to claim 5, characterized in that: The temperature of the cross-linking reaction is 10° C. to 50° C., and the time of the cross-linking reaction is 5 h to 24 h.
17. The method for preparing a microcarrier according to claim 6, characterized in that: The concentration of the fourth hydrophilic organic solvent is 100%.
18. A microcarrier prepared by the method according to any one of claims 1 to 17, characterized in that: The cross-linking degree of the microcarrier is greater than 50%, the diameter of the microcarrier is 10 μm to 1000 μm, the porosity of the microcarrier is greater than 85%, and the charge density of the microcarrier is -50 μeq / g to +71 μeq / g.
Citation Information
Patent Citations
Injectable hyaluronic acid microsphere as well as preparation method and application thereof
CN113663126A
Cationic microsphere and preparation method thereof
CN115845120A